Experience of application 0.1% methylprednisolone aceponatе in a complex therapy chronic dermatoses - Y. S. Kondratyeva; V. V. Karchova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The review describes the structure and pharmacokinetics of 0.1% methylprednisolone aceponate, world's data practice, showing high efficiency and safety of this drug in the treatment of chronic dermatoses, presents the results of study the therapeutic efficacy of different medicinal forms.